Assessment of the Impact of Chinese and Indian Economic Activities in Africa: A Particular Focus on Ethiopia's Economy. (August 2019) - Addis, Amsalu K.; Zuping, Zhu
In Africa, China and India are considered to be following a donor–recipient approach and are explicitly criticised for exploiting the continent's energy resources. This study focuses on the presence of the Asian countries in terms of institutional theory, historical connections, instrumental motivations and political engagement with Africa in general, and with Ethiopia in particular. India offers non-pecuniary value, such as scholarship and technical assistance, whereas China focuses on a wider range of economic aids and non-pecuniary packages; thus, both countries are well positioned in Africa. This study is an exercise audit of the impact of Chinese and Indian economic activities on Ethiopia's economic growth and examines the period from 1992 to 2016 from historical and contemporary perspectives. This study also includes a case study of members of Ethiopian society's attitudes towards the presence and prospects of Chinese and Indian investment projects and its perceptions of these projects. Although some long-term developmental impacts remain uncertain, this study argues that the presence of the Asian drivers has favoured Ethiopia in many investment sectors and concludes that the overall impact of the Asian drivers on Ethiopia is beneficial. To collect primary data, individual and group interviews and discussions were conducted.